Comparative study on the short-term effects of audio and visual raptor presence on a pigeon population, with a view towards pest control. Issue 1 (2nd January 2020) - Harris, Emma; de Crom, Engela P.; Fouche, Jacques; Wilson, Ann
Abstract: A study on the short-term effects of audio raptor recordings and the visual presence of raptors, as a means of pigeon control on the University of South Africa's Muckleneuk campus was conducted over a 12-week period in 2014/2015. This study recorded no significant difference in the number of pigeons between the scare treatments, however significant difference was observed within the 30 minute period post-scare at dawn resulting in temporary behavioural modification. Knowledge of pigeons' response to audio and visual raptor presence contributes to understanding pigeon ecology and integrative pigeon control strategies.